Analisis Mekanisme Penetapan Harga Dalam Perspektif Ekonomi Syariah Di Pasar Tradisional Indonesia: Studi Literatur Sistematik - Prasetia, Hary Yuda; Wiharto, Nardi; Mulyani, Sari (Green Publisher Indonesia, 2025)
This research analyzes the pricing mechanisms in traditional Indonesian markets from the perspective of Islamic economics, emphasizing the principles of justice (ʿadl), public interest (maṣlaḥah), and the prohibition of exploitative practices such as iḥtikār (hoarding) and ghabn fāḥiḥ (excessive markup). The systematic literature study methods was used to synthesize findings from 20 journal articles and policy documents. The results show that 68% of traders apply the cost-plus pricing method with a fair margin of 10–20%, which aligns with the concept of ribh al-maʿrūf. However, 22% of cases indicate hoarding practices and excessive markups, especially on seasonal commodities. Transparent bargaining practices also contribute to the formation of fair prices. This research proposes a selective tasʿīr model as a regulatory intervention and recommends tasʿīr-based training as well as increased supply chain transparency. These findings contribute both theoretically and practically to the development of a contextual and fair Sharia pricing system in Indonesia's traditional markets.